Open educational resources: an analysis of Minnesota State Colleges and Universities student preferences. (2nd September 2018) - Kinskey, Caroline; King, Hunter; Lewis Miller, Carrie
ABSTRACT: The cost of college tuition and textbooks continues to rise and can function as a barrier to education for many students. This study evaluated Minnesota State Colleges and Universities students' attitudes towards different types of learning material (e.g. commercially printed textbooks, eBooks and open educational resources (OERs)) and class type preferences (e.g. on-campus, hybrid and online). In addition, students indicated that they had ever chosen not to purchase a required textbook as well as how much they pay on average for a single textbook and approximately how much they paid for textbooks in the most recent semester. Cost was noted as a common deterrent; however, a more frequent reason provided by students for not buying a textbook was being able to adequately complete assignments without the textbook. This indicates that instructional method might be more of an issue than cost. OERs would lower these costs, but few students have been exposed to this kind of learning material and the overall impact on teaching quality is still largely unknown. The differences between two-year institutions and four-year institutions are examined and ideas to remedy the problem are noted.